Analisis Faktor-faktor yang Mempengaruhi Penerimaan Pengguna QRIS di Indonesia - Safira Noor Andinia; Graha Prakarsa; Vani Maharani Nasution (Universitas Binaniaga Indonesia, 2023)
The research is based on the problem that the existence of QRIS as a new option on digital payments is still unable to tempt the public to use it in daily payments. This research aims to discover the acceptance of QRIS to its users in Indonesia using the technology acceptance model with information quality and service quality as external factors. The data analysis technique used is Partial Least Squares - Structural Equation Model using the software SmartPLS 3.0. Data collection technique were obtained through online questionnaires to QRIS users in Indonesia and involved 532 respondents. Based on the results of the data analysis, it shows that information quality and service quality have a significant positive effect on perceived usefulness and have an intermediate influence of 40%, information quality and service quality have a significant positive effect on perceived ease of use and have an intermediate influence of 44,9,%, perceived usefulness and perceived ease of use have a significant positive effect on continuance intention to use and have an intermediate influence of 39,9%, and continuance intention to use have a significant positive effect on actual system use and have an intermediate influence of 37%.